Analisis Hak Atas Perlindungan Serta Pengawasan Terhadap Data Pribadi Pada Proses Penegakkan Hukum - Faturohman Faturohman; Ratu Suci Nurrachmah; Ridwan Mohammad (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Protection of personal data is an embodiment of a guarantee of human rights, privacy and inviolability. The state has a full obligation to respect each other and respect the rights of every human being, as regulated in statutory regulations. Regulations regarding the protection of personal data owned by every human being, there is confusion and overlap due to the many regulations that have been established. The government, together with related officials, has formulated a draft law regarding the protection and supervision of the personal rights of every human being. This protection and supervision aims to cover the exception of personal data on the basis of a legitimate public interest, including law enforcement purposes. Arrangements that are carried out in a balance between the interests of law enforcement of a crime and the protection and supervision of the personal data of every human being, are expected to avoid actions that are carried out arbitrarily.